Unlocking Micro Enterprises Potential Amid Structural Barriers: The Mediating Role of Digital Financial Capabilities on Financial Literacy and Access to Financing - Afini Gusti; Hais Dama; Mohamad Agus Salim Monoarfa (Universitas KH. Abdul Chalim Mojokerto, 2026)
Micro businesses still face limitations in financial literacy, access to financing, and the use of financial technology that affect business performance. This study aims to analyze the influence of financial literacy and access to financing on the performance of micro businesses with digital financial capabilities as a mediating variable in micro business actors in Gorontalo City. The study used a quantitative approach using the PLS-SEM method on 150 respondents selected through purposive sampling. Data were collected through interviews using a questionnaire with a semantic differential scale of 1–7 and analyzed using SmartPLS 3. The results of the study show that financial literacy and access to financing have a positive effect on digital financial capabilities and micro business performance. Digital financial capabilities also have a positive effect on business performance and mediate the influence of financial literacy and access to financing on the performance of micro businesses. Keywords: financial literacy, access to financing, digital finance capabilities, micro business performance